Graphene wrapped Y2O3 coated LiNi0.5Mn1.5O4 quasi-spheres as novel cathode materials for lithium-ion batteries - Hanan Abdurehman Tariq (14778361) (2021)
LiNi0.5Mn1.5O4 with a high-voltage spinel structure is a potential cathode material for high-energy lithium-ion batteries (LIBs). Y2O3 coated quasi-spheres of LiNi0.5Mn1.5O4 covered in graphene (LNMO-YO-G) have been synthesized by a microwave-assisted chemical co-precipitation technique. The coating of quasi-spheres with Y2O3 and subsequent wrapping in graphene nanosheets does not modify the bulk structure and inhibits the production of undesirable phases. Thermal analysis indicates that the developed materials demonstrate good thermal stability. The material exhibits an initial capacity of 133 mAh g−1 at the C/10 rate with a capacity retention of 98% after 100 cycles. Remarkably, a discharge capacity of 115 mAh g−1 is achieved in LNMO-YO-G at a 10C rate, reflecting its extraordinary improvement in the rate capability. Furthermore, after 20 cycles at higher temperature (55 °C), the cathode samples exhibit an excellent capacity of 132 mAh g−1. Y2O3 coating reduces the leaching of ions from the electrode, but such coatings reduce the electrical conductivity. Conversely, graphene increases the electrical conductivity, wraps the active particles along an electrically conductive path, and prevents agglomeration. Parasitic reactions are inhibited without compromising electrical conductivity due to the synergistic material design and fast microwave synthesis method. The proposed material synthesis strategy can be effectively extended to other classes of electrode materials to improve their cyclic performance. Other Information Published in: Journal of Materials Research and Technology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jmrt.2021.07.038